Penoscrotal Hypospadias, A 4- Year Follow-Up - Danu Caraka Alam; Dodo Wikanto (Jurnal Kedokteran Brawijaya, 2021)
Penoscrotal hypospadias, a severe congenital abnormality, can interfere with urinary, sexual, and aesthetic functions. This paper reports a 2-year follow-up of a penoscrotal hypospadias after urethroplasty using the Koyanagi-Nonomura technique. After surgery, there are some complication of urethrocutaneus fistula and infectio. This patient undergoes urethrocutaneus fistula repair and chateter was inserted into the new urethra which was resulted in normal urination function and penis size.